Student Entrepreneurship in Accounting: Enhancing Vocational Internships to Achieve SDGs 4 and 8 - Rosy Aprieza Puspita Zandra (Westscience Press, 2025)
Student entrepreneurship serves as a catalyst for innovation and sustainable development, aligning with Sustainable Development Goals (SDGs) 4 (Quality Education) and 8 (Decent Work and Economic Growth). This paper explores the integration of entrepreneurial internships within the accounting education framework, highlighting their potential to address gaps in vocational training and enhance students' technical and non-technical competencies. By leveraging a qualitative case study approach, the study identifies critical gaps in curriculum alignment, industry expectations, and evaluation mechanisms, proposing a competency-based assessment model tailored for vocational education. This model is designed to bridge academic and industry demands while supporting SDG objectives through improved educational and employment outcomes.